Foreigners in Polish prisons. The law and practice of taking into account cultural differences (Biuletyn Kryminologiczny, 2021)
Polish executive law allows for the possibility of implementing an individualised approach to imprisonment in a system encompassing programmed, therapeutic or normal rehabilitation. Polish laws take into full account the Convention's standards on the prohibition of torture and other cruel, inhuman or degrading treatment or punishment, adopted by the United Nations General Assembly in 1984 and the European Prison Rules issued by the Council of Europe. There are no specific provisions in Polish legislation relating to the imprisonment of foreigners, however, the guarantees of respect for dignity and cultural distinctiveness arise directly from the general principles for imprisonment. The number of foreigners incarcerated in Polish prisons is small. Every year, approximately 7,000 foreigners are convicted in Poland. Of this group, on average, 300 are servinga prison sentence. In this article we will outline the characteristics of this group of convicted criminals based on the available statistical data and in relation to the regulations in effect in Poland.Polskie prawo wykonawcze zapewnia możliwość realizacji zasady indywidualizmu w odbywaniu kary pozbawiania wolności. Kara ta może być odbywana w systemie programowanego oddziaływania, terapeutycznym lub zwykłym. Polskie przepisy w pełni uwzględniają standardy Konwencji w sprawie zakazu stosowania tortur oraz innego okrutnego, nieludzkiego lub poniżającego traktowania lub karania, przyjętej przez Zgromadzenie Ogólne Narodów Zjednoczonych w 1984 roku oraz Europejskich Reguł Więziennych wydanych przez Radę Europy. W polskim ustawodawstwie nie ma przepisów szczególnych, które dotyczyłyby odbywania kary pozbawienia wolności przez cudzoziemców, jednak gwarancje poszanowania ich godności i odrębności kulturowych wynikają wprost z ogólnych zasad wykonywania kary pozbawienia wolności. Liczba cudzoziemców odbywających karę pozbawienia wolności w polskich zakładach karnych jest niewielka. Każdego roku prawomocnie skazywanych w Polsce jest około 7000 cudzoziemców. Z tej grupy przeciętnie 300 odbywa karę pozbawienia wolności. Artykuł przedstawia charakterystykę tej grupy skazanych w oparciu o dostępne dane statystyczne oraz w odniesieniu do obowiązujących w Polsce przepisów.